Analisis Pemasaran Komoditi Okra di Desa Lemoabo Kecamatan Kusambi Kabupaten Muna Barat - Wa Ode Lisma; Sitti Rahma Ma'mun; Asriani Asriani (Fakultas Pertanian Universitas Muhammadiyah kendari, 2022)
This research was conducted in Lemoambo Village, Kusambi District, Muna Barat Regency from May to June 2021. The purpose of this study was to determine the pattern of the Okra marketing channel, to calculate the margin of the Okra marketing channel and to determine the efficiency of the Okra marketing in Lemoambo Village. Twenty five samples were taken from Okra farmers and 3 traders. All Okra farmers were included in the survey while the traders sample were taken using the snowball method, i.e. trader respondents was chosen based on information obtained from farmers. The data analysis technique used in this research is data analysis with descriptive methods. The result shows that there are two marketing channels used by Okra farmers in Lemoambo Village. The number of farmers who market Okra in marketing channel one is eleven people with a marketing margin of Rp 2.000/Kg with marketing efficiency of 67% while in marketing channel two the number of farmers who market Okra is fourteen people with a large marketing margin of Rp 4.500/Kg with a marketing efficiency of 48%.